Description of the puparium and redescription of the imagoes of Chorophthalmyia brevicornis Lindner (Diptera: Stratiomyidae) - Pujol-Luz, José Roberto; Lopes, Welinton Ribamar; Viana, Gustavo Glória (Zootaxa, 2016)
The puparium of Chorophthalmyia brevicornis is described for the first time, based on five puparia. Larvae of the species were reared in the laboratory under semi-controlled conditions until the emergence of the adults. In addition, to the description of the puparium we provide a redescription of the imagoes of C. brevicornis.